Analisis Kekosongan Hukum Terhadap Transportasi Berbasis Aplikasi: Studi Kasus Ojek Online - Agustine, Sharleen (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Legal Vacuum Analysis in App-Based Transportation: A Case Study of Online Ojek. The rise of app-based transportation services, such as online motorcycle taxis (ojek online), which are increasingly favored by the public. However, the rapid growth of these innovations has not been accompanied by adequate regulatory clarity, resulting in a legal vacuum in their governance. This vacuum has led to various issues, including the unclear legal status of drivers and weak legal protection for consumers and workers. This study aims to analyze the forms of legal vacuum occurring in the app-based transportation sector and its impact on legal certainty and social justice. The research employs a qualitative approach using a literature review method to understand the legal gaps in regulating app-based transportation, particularly online ojek. indicate the absence of a specific legal framework for online-based transportation, leading to overlapping institutional authorities and uncertainty in law enforcement. Therefore, regulatory reform is urgently needed to address legal demands in the era of digital transformation in the transportation sector.